2023
DOI: 10.1002/alr.23142
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intranasal corticosteroid treatment induces degeneration of olfactory sensory neurons in normal and allergic rhinitis mice

Abstract: BackgroundNasal eosinophilic inflammation is the therapeutic target for olfactory dysfunction in allergic rhinitis (AR). Intranasal corticosteroids are commonly considered to offer targetable benefit given their immunosuppressive property. However, experimental evidence suggests that continuous corticosteroid exposure may directly cause olfactory damage by disrupting the turnover of olfactory sensory neurons (OSNs). This potentially deleterious effect of corticosteroids calls into question their long‐term topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Furthermore, there are unexpected findings that topical corticosteroids may reduce olfactory function by inducing neuronal apoptosis and OSN turnover disturbance ( Takanosawa et al, 2009 ; Crisafulli et al, 2018 ). In an allergic rhinitis mouse model, intranasal fluticasone propionate treatment improves olfactory function and reduces EOS-associated inflammation in OM but fails to rebuild a mature OSN population ( Li et al, 2023 ).…”
Section: Mechanisms Of Eos-induced Osn Damagementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there are unexpected findings that topical corticosteroids may reduce olfactory function by inducing neuronal apoptosis and OSN turnover disturbance ( Takanosawa et al, 2009 ; Crisafulli et al, 2018 ). In an allergic rhinitis mouse model, intranasal fluticasone propionate treatment improves olfactory function and reduces EOS-associated inflammation in OM but fails to rebuild a mature OSN population ( Li et al, 2023 ).…”
Section: Mechanisms Of Eos-induced Osn Damagementioning
confidence: 99%
“…Slight or moderate OSN loss without detectable OD in patients with CRS can lead to reduced OB volumes ( Rombaux et al, 2008 ). Results from the murine OD model imply that the decline of olfactory function can be detected only when OSN loss reaches a certain level ( Li et al, 2023 ). Changes in OB size are more sensitive than OD in detecting OSN loss in patients with CRS.…”
Section: Mechanisms Of Eos-induced Osn Damagementioning
confidence: 99%
“…Lamanthia and colleagues have demonstrated that retinoic acid (RA), a member of the steroid/thyroid signaling molecule superfamily, serves as a significant regulatory factor in morphogenesis, differentiation, and regeneration in mammalian olfactory pathways [ 67 ]. However, studies indicate that intranasal corticosteroid treatment for 8 weeks (FP-wk8) can diminish the odor sensitivity of normal mice, suggesting that prolonged intranasal corticosteroid treatment may lead to degeneration of olfactory sensory neurons, thereby affecting treatment efficacy [ 68 ].…”
Section: Clinical Treatment Of Olfactory Dysfunctionmentioning
confidence: 99%
“…While considered safe a negative impact on paediatric growth is discussed in the literature 142,143 . Further, chronic intranasal corticosteroid treatment is associated with impaired olfactory function due to neuronal degeneration 144 …”
Section: Neuroendocrine Control Of the Ob And Metabolismmentioning
confidence: 99%